The Reasons of Farmers Marketing and the Motivation Of Farmers to Maintain Bali Cowards in the Covid-19 Era - Ayu Gemuh Rasa Astiti, Ni Made (Green Publisher Indonesia, 2022)
Covid-19 has damaged the world economy, including the economy of farmers. So that farmers survive the waves of Covid-19, many farmers sell cattle. The habit of farmers who sell their feeder livestock when they need large funds, so the price of feeder cattle sold is relatively cheap, because it determines the price is in an intermediary trader (blantik). The purpose of this study is to determine the causes of breeders who sell their feeder cattle and to analyze the marketing channel of feeders. This research is exploratory research through qualitative and quantitative combinations and combinations. This study was conducted on feeder cattle breeders who had sold their feeder cattle in Sembung Village, Mengwi, Badung. The study location was chosen intentionally (purposive sampling). The research instrument or measurement instrument used as an interview guide to help get answers from respondents is a structured and closed questionnaire that is equipped with open questions. The conclusion of this study is the tendency of farmers to sell their feeder cattle because of the need for school fees for children 30%, traditional ceremonial fees (marriage, odalan, dental slaughtering) 13.75%. Home repair costs 12.50%, medical costs 15%and daily consumption costs 28.75%. . Meanwhile: Farmers' motivation to increase cattle is for family savings by 41.25%, the use of agricultural waste is 22.50%, utilizing 23.75% from leisure time and increasing family income by 12.50% by increasing income that leads to welfare family.